«Disunito fragoroso, incalzante»: l’irruzione del passato nella vita di un «personaggio che sembra cechoviano». Su Registrazione di eventi (1964) di Roberto Roversi - Toracca, Tiziano (L'ospite ingrato, 2024)
The contribution focuses on Registrazione di eventi (1964) by Roberto Roversi, reconstructing its critical reception, focusing mainly on the novel’s experimental character, and hypothesizing a resemblance to other Italian novels of the 1960s and 1970s in light of the category of Neomodernism. From this perspective, starting with a comparison with a Chekhov’s novella (A Gentleman Friend) and a reflection on some key oppositions in the text, the two main themes of the novel, the protagonist’s destitution and his traumatic relationship with the past, are explored.